Improved properties of near-eutectic nickel silicide alloyed with vanadium, chromium, and carbon in inductively coupled plasma spheroidization for additive manufacturing - Foysal Kabir Tareq; Geir Grasmo (Materials & Design, 2025)
Nickel-rich silicides offer excellent hardness, thermal stability, corrosion and wear resistance. However, their application is limited by poor fracture resistance and a propensity for cracking, particularly when processed through conventional thermo-metallurgical methods. To address these limitations, this study explores the enhancement of nickel-silicon alloy properties through alloying with V (5 wt%), Cr (3 wt%), and C (0.3 wt%). The Ni-12Si alloy features a Niss-Ni3Si eutectic with a γ-Ni31Si12 phase. Alloying elements refine the microstructure, are present as soluble constituents in the phases, stabilizing the γ-Ni31Si12, and introducing element-rich phase precipitation. Additionally, plasma spheroidization of these as-crushed powder was performed to improve powder characteristics for additive manufacturing. The spheroidization process, optimized by adjusting plasma power and powder feed rate, yields spherical powders with refined microstructures, and improved flowability, showing suitability for laser-based directed energy deposition (DED-LB). DED-LB deposition of spheroidized powders on S355 steel substrate showed the Ni-12Si bead exhibited solidification microcracks at the grain boundaries, whereas the alloyed variants Ni-11.4Si-5V, Ni-11.1Si-3Cr, and Ni-12Si-0.3C demonstrated flawless deposits with improved properties. These enhancements are attributed to the synergistic effects of alloying on phase evolution, microstructural refinement and transformation, and grain boundary modification through the formation of fine, element-rich precipitates at grain boundaries.